Osteosarcopenia in rheumatoid arthritis treated with glucocorticosteroids – essence, significance, consequences - Marcin Radkowski (Termedia Publishing House, 2020)
Rheumatoid arthritis (RA) is one of the most common rheumatic diseases, associated with cooccurrence of serious side effects. This study discusses the problems associated with chronic RA, well-known as osteoporosis, but also recently recognized as sarcopenia. Relationships between sarcopenia and rheumatic diseases are not yet fully understood. Co-occurrence of osteoporosis and sarcopenia, referred to as osteosarcopenia, is becoming increasingly important. The overlap of the effects of RA and osteosarcopenia and the adverse effects of glucocorticosteroids leads to progressive impairment of the musculoskeletal system, increasing the risk of falls, fractures, institutionalization and death, and it is a source of dramatic socioeconomic burden on society. Very limited options for effective treatment of developed osteosarcopenia, as well as the severity of complications caused by it, advocates for the need of broad education and raising public awareness, especially among health care workers, in order to implement the prevention of osteosarcopenia as early as possible.